Fotografias e territorialidades : memórias e resistências sobre a comunidade de Monteiro/São Martinho - Simões, Elizabeth Nader (2018)
This work analyzes photography as a source of documentations that perpetuate moments, witness individual and collective routine, feed and produce memories and serve as a resistance to forgetfulness and silence. Based on the photo documentary - developed by this researcher - held in two distinct moments of the 34 families of the Monteiro - São Martinho community (municipality of Anchieta, south coast of the State of Espírito Santo, Brazil) during their process of territorial changing, caused by the Vale S/A's intention of building Companhia Siderurgica Ubu (CSU) in the area. The first moment, made in the period between 2012 and 2014, records the daily life of the residents before the process of deterritorialization of the neighborhood Monteiro; the second moment, from 2016, monitors the reterritorialization process of the families in a new residential complex (built by the mining company Vale S/A specially for them, in the São Martinho district), regarding what has changed, what has remained and what no longer exists in the quotidian activities of the residents. It is intended to create an analysis on the practical actions during a process of deterritorialization / reterritorialization of the community, in these different moments, by the perspective of photography / visual documentation. The images are understood here as tools for understanding the complexity of this whole process of territorial entanglements between institutional formalities and everyday creations.